2018
DOI: 10.1021/acscentsci.7b00475
|View full text |Cite
|
Sign up to set email alerts
|

REDOR NMR Reveals Multiple Conformers for a Protein Kinase C Ligand in a Membrane Environment

Abstract: Bryostatin 1 (henceforth bryostatin) is in clinical trials for the treatment of Alzheimer’s disease and for HIV/AIDS eradication. It is also a preclinical lead for cancer immunotherapy and other therapeutic indications. Yet nothing is known about the conformation of bryostatin bound to its protein kinase C (PKC) target in a membrane microenvironment. As a result, efforts to design more efficacious, better tolerated, or more synthetically accessible ligands have been limited to structures that do not include PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…39 By tracking the redox behavior of the Ni atoms, the state-of-charge of the battery may be directly assessed and, if desired, be constrained to a range which avoids the formation of undesirable Ni species. In the present instance, comparison to previously reported empirical standards 3,40,41 suggest that the present Ni oxidation state is between +2 and +3 in the discharged state and between +3 and +4 at full charge. Moreover, a strictly lateral displacement devoid of any isosbestic points suggests that the entirety of the Ni atoms evolve in concert rather than forming a linear combination, indicating a solid solution behavior rather than a mixed-phase behavior.…”
Section: Resultssupporting
confidence: 77%
“…39 By tracking the redox behavior of the Ni atoms, the state-of-charge of the battery may be directly assessed and, if desired, be constrained to a range which avoids the formation of undesirable Ni species. In the present instance, comparison to previously reported empirical standards 3,40,41 suggest that the present Ni oxidation state is between +2 and +3 in the discharged state and between +3 and +4 at full charge. Moreover, a strictly lateral displacement devoid of any isosbestic points suggests that the entirety of the Ni atoms evolve in concert rather than forming a linear combination, indicating a solid solution behavior rather than a mixed-phase behavior.…”
Section: Resultssupporting
confidence: 77%
“…In a separate study, a combination of REDOR NMR and molecular dynamics simulations identified a distribution of PKC-bound bryostatin conformers (Fig. 1c), a feature that was unique to the bryostatin scaffold and not observed in a phorbol ester derivative 56 . Together, these studies suggest that the multiple PKC-bound conformers available to the bryostatin scaffold could generate differential orientations of the activated PKC-ligand complex and influence PKC's interactions with downstream effector proteins, thereby explaining bryostatin's unique biological activity.…”
Section: Resultsmentioning
confidence: 92%
“…Our computational studies revealed that hydrogen-bonding functionalities around the C-ring subunit of the bryostatin scaffold, specifically the C1 carbonyl, C26 hydroxyl and C19 hemiketal, are spatially preorganized by the A and B rings into a binding conformation that mimics PKC's endogenous ligand, DAG ( Fig. 1a) [54][55][56]61 . Indeed, seminal studies by our group showed that modification or deletion of any of the C1, C26 and C19 functionalities reduced or eliminated PKC binding while changes in the A-and B-rings generally had little or no effect on binding, suggesting that changes to these subunits could be used to change physical properties, biological function and biodistribution and thereby potentially improve efficacy and tolerability 20,54,[61][62][63][64] .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations